Conflictogenic situation of the global world: incompatibility of institutions instead of clash of civilizations - Ekadumov, Andrew I. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
Nation-states remain key players in global politics. However, in a globalised world, politics is being implemented in a transnational space. Local-civilizational and civilization-stage concepts of sociodynamics lay claim to understanding transnational conflicts in the post-national era. The emergence of preconditions for conflict-generating processes is explained by the incompatibility of local-civilizational identities or the discrepancy between the technical and institutional organisation of agrarian, industrial, and post-industrial civilizational waves. In the global space of flows that has transformed the political and economic space of places, elements of various civilizational complexes, considered from both local-civilizational and civilization-stage research perspectives, are situationally combined, which prevents the identification of the essential factor initiating conflicts on a subnational, national, and supranational scale within the context of the civilizational approach. An alternative to the indicated civilizational concepts is the concept of limited and open access social orders, which describes two mutually exclusive institutional systems that coexist in a global world but differ fundamentally in the organisation of violence, as well as the production and distribution of wealth. In the proposed research perspective, global conflict-generating processes are not manifestations of a clash of civilizations, but rather the consequence of the coexistence of two mutually exclusive modes of inclusion and the organisation of violence in a context of deterritorialisation.
Keywords: open access order; limited access order; civilization; space of flows; conflict